Camelot : a role playing simulation for political decision making - Woodworth, James R. (Harcourt Brace, 1994)
This text helps you experience the excitement and challenge of politics at the local level. In this innovative book, readers are cast in the role of city council and planning commission members responsible for managing Camelot, a medium-sized and socio-economically integrated city.